Diplomatie aus dem Untergrund: Die merkwürdige Karriere des Alexander (Maurus) Horn(e) (1762 - 1820) - Oberhauser, Claus (2021)
Alexander (Maurus) Horn was a monk, book agent, secret agent and diplomat in a time of great upheaval. He had a key role in a British information-gathering network. Looking at history through his lens, one leaves the negotiating tables of high diplomacy and dives into the world of seemingly secondary actors in European diplomacy.